2019
DOI: 10.1016/bs.ctdb.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The evolution and patterning of male gametophyte development

Abstract: 1. The evolutionary history of the male gametophyte 1.1. The origins of spermatogenesis in green plants 1.2. The sporophyte was key for terrestrial plant evolution 1.3. Heterospory and the origin of microgametophytes 1.4. Adaptations of seed plant microgametophytes 2. Male germline development in angiosperms 2.1. Asymmetric division and cell fate determination 2.2. Cell cycle control and male gametophyte patterning 2.3. Transcriptional control of male gametophyte patterning 2.4. Chromatin remodelling in male g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 209 publications
(270 reference statements)
1
69
0
Order By: Relevance
“…Conversely, bryophytes, lycophytes, monilophytes, and some gymnosperms such as ginkgoes and cycads utilize motile male gametes called spermatozoids, which are equipped with two or more flagella, for sexual reproduction (Southworth and Cresti, 1997;Renzaglia and Garbary, 2001). In both cases, drastic reorganization of cellular components occurs during male gamete development (Hackenberg and Twell, 2019). In the angiosperm, A. thaliana, four haploid microspores are produced by meiosis of a diploid pollen mother A B FIGURE 1 | Scheme of macroautophagy.…”
Section: Male Reproduction In Land Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, bryophytes, lycophytes, monilophytes, and some gymnosperms such as ginkgoes and cycads utilize motile male gametes called spermatozoids, which are equipped with two or more flagella, for sexual reproduction (Southworth and Cresti, 1997;Renzaglia and Garbary, 2001). In both cases, drastic reorganization of cellular components occurs during male gamete development (Hackenberg and Twell, 2019). In the angiosperm, A. thaliana, four haploid microspores are produced by meiosis of a diploid pollen mother A B FIGURE 1 | Scheme of macroautophagy.…”
Section: Male Reproduction In Land Plantsmentioning
confidence: 99%
“…Spermatozoids move toward female gametes in water to accomplish fertilization (Shimamura, 2016). Although the molecular mechanisms of male reproduction in angiosperms are well-documented, molecular mechanisms of spermatozoid formation in basal land plants remain mostly ambiguous (Hackenberg and Twell, 2019).…”
Section: Male Reproduction In Land Plantsmentioning
confidence: 99%
“…In the unicellular algal model organism Chlamydomonas reinhardtii flagella are responsible for motility of the organism and serve during sexual reproduction to mediate a species-specific adhesion between two cells of different mating types (van den Ende et al 1990). In streptophyte algae (Streptophyta comprise charophycean green algae as well as land plants), male gametes (spermatozoids) are the only motile cells of sessile multicellular algae, swimming to the oogonia to fertilize the egg cell (Hackenberg et al 2019, McCourt et al 2004. After the water-to-land-transition of plants this system was retained, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis has revealed that the R2R3 S18 GAMYB family is sister to the DUO1 R2R3 MYB family (Du et al , ; Higo et al , ). The GAMYB and DUO1 R2R3 MYB family are clearly separated in moss and liverworts, with DUO1 directing male germline development and the GAMYB clade specializing male reproductive roles in angiosperms (Higo et al , ; Hackenberg and Twell, ).…”
Section: Discussionmentioning
confidence: 99%